Spontaneous Urethral Laceration in a Patient Experiencing Acute Ulcerative Colitis Flare - Ryan Morris; John Barnard; Chad Morley (Case Reports in Urology)
Spontaneous urethral laceration in the female without associated external trauma is an exceedingly rare phenomenon. Most cases are related to childbirth or the presence of a concomitant pelvic fracture or penetrating injury. Herein, we present a novel case of spontaneous urethral laceration in a female which happened to occur during an acute flare of her previously diagnosed ulcerative colitis. The diagnosis of spontaneous urethral laceration is rare, and underlying etiology is often uncertain.